(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2014)
The article analyses the possibilities of verbalization of different information in the nominal structure of compound nouns of German. Compound nouns contain factual (rational) and pragmatic (evaluative and expressive) information about a referent. Informational intenseness of noun compounds is used in media texts for informing of reader and forming of corresponding attitude toward the object of nomination.